META-ANALYSIS OF FOCUSKY LEARNING MEDIA ON STUDENT LEARNING OUTCOMES - Susana Puspita; Irfandi Irfandi (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2022)
Learning media is a means used by educators to support the learning process activities to achieve the expected goals. Student learning outcomes can be influenced by the use of interesting and easy-to-understand learning media for students, one of which is Focusky. The Focusky application will produce learning media that can stimulate student learning styles with the advantages of the drag and drop method. The method used is a meta-analysis by reviewing articles published in national journals related to Focusky learning media. The data analysis used is qualitative data analysis for the data from the narrative study of the studies found. The sample used was 10 articles in national journals about focusky learning media. The results of the meta-analysis of national journals show that learning using focusky-based learning media has an effect on student learning outcomes.